What is a Good Way to Visualize the Positive Correlation between Two Numerical Variables? - Heru Santoso Wahito Nugroho; Sanglar Polnok; Tanko Titus Auta; Ambo Dalle; Bahtiar Bahtiar; Pius Selasa; Koekoeh Hardjito; Atik Badi’ah; Fransiskus Salesius Onggang; I Putu Suiraoka; Alfian Helmi; Supriyanti Supriyanti; Azwarni Azwarni (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Most of the results of correlation analysis between variables are not equipped with visualization, so it is deemed necessary to explain how best to visualize the results of correlation analysis, especially for numerical variables. In this case, the best way to present correlations between numerical variables is a scatter diagram. If the points on the diagram are closer to the straight line, the higher the correlation coefficient, meaning that the degree of correlation is getting stronger. In this case, the positive correlation is indicated by the line from the lower left to the upper right. This visualization helps clarify the reader's understanding of the results of the correlation analysis, as well as being a valuable lesson for their similar research projects. Keywords: positive correlation; correlation coefficient; visualization; scatter diagram